Cordierite ceramic material as well as preparation method and application thereof

Cordierite ceramic materials are prepared by mixing ferrochrome waste slag and fly ash in a specific proportion and combining with SnO2, cordierite ceramic materials are prepared through calcination, which solves the problem of insufficient quality content of cordierite phase in the existing materials, and achieves significant improvements in high-temperature performance and mechanical properties.

CN120157467AActive Publication Date: 2025-06-17JINGDEZHEN CERAMIC UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510501404.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-06-17
Estimated Expiration
2045-04-21

AI Technical Summary

Technical Problem

The cordierite phase mass content in existing cordierite ceramic materials is small, resulting in poor high-temperature performance and mechanical properties.

Method used

By mixing iron chromium waste slag and fly ash in a specific proportion, heating to obtain a molten mixture, quenching treatment, mixed with SnO2, and calcined to prepare cordierite ceramic material. The process includes preheating, first calcination and second calcination, controlling the heating rate to inhibit crystallization of the spinel phase.

Benefits of technology

The quality content of the cordierite phase in cordierite ceramic materials is improved, and the high temperature and mechanical properties of the material are significantly improved, including low thermal expansion coefficient, high flexural strength and excellent thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120157467A_ABST
    Figure CN120157467A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of cordierite materials, and particularly relates to a cordierite ceramic material as well as a preparation method and application thereof. The preparation method of the cordierite ceramic material comprises the following steps: 1) mixing ferrochrome waste residue and fly ash according to a mass ratio of (3-5): (5-7), heating to obtain a molten mixture, and then carrying out water quenching treatment to obtain a frit raw material; and 2) mixing the obtained frit raw material with SnO2 according to a mass ratio of (95-99): (1-5), grinding, and calcining to obtain the cordierite ceramic material, the calcination treatment comprises preheating, first calcination and second calcination, and the heating rate from preheating to first calcination is 8-12 DEG C / min. The whole process is matched, and the obtained cordierite ceramic material is high in cordierite phase mass content, low in thermal expansion coefficient, high in bending strength, excellent in thermal stability and good in high-temperature performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cordierite material preparation, and particularly relates to a cordierite ceramic material, a preparation method thereof, and an application thereof. Background Art

[0002] Magnesium aluminate spinel (MgAl2O4), as a cubic spinel-type oxide, in which Al 3+ and Mg 2+ respectively occupy the octahedral and tetrahedral interstitial sites of oxygen to form a three-dimensional oxygen close-packed framework, endowing the material with excellent high-temperature stability (melting point > 2100 °C) and chemical inertness. However, during the crystallization process of cordierite ceramics (Mg2Al4Si5O 18 ), the formation of magnesium aluminate spinel often occurs, and its formation mechanism is closely related to the deviation of the Mg / Al molar ratio in the cordierite precursor from the theoretical value, the local temperature gradient, and the uneven mixing of raw materials. This by-product will significantly deteriorate the macroscopic properties of the material and become the core bottleneck restricting the industrialization of high-end cordierite-based materials. Experimental data show that when the spinel volume fraction > 5%, the flexural strength of cordierite decays by 28% - 32%, and the thermal shock stability deteriorates by 35% - 40%. The essential mechanism lies in that the covalent bond energy of the Si-O bond in the cordierite structure (> 800 kJ / mol) is significantly higher than that of the Al-O (511 kJ / mol) and Mg-O bonds (394 kJ / mol), resulting in magnesium aluminate spinel preferentially occupying the Al 3+ / Mg 2+ coordination sites through lattice matching, blocking the construction of the Si-O-Al / Mg network and forming a kinetic barrier. Although the existing external flux method (such as adding B2O3, Li2O, TiO2) used in the preparation of cordierite ceramic materials can promote the decomposition of magnesium aluminate spinel, the introduced borate glass phase will reduce the refractoriness of the material (≥ 200 °C) and form low-melting-point regions in the microstructure, damaging the high-temperature performance. As a result, the mass content of the cordierite phase in the existing cordierite ceramic materials is relatively small, and it is easy to cause problems of poor high-temperature performance and mechanical performance. Summary of the Invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects that the mass content of the cordierite phase in the existing cordierite ceramic materials is relatively small and it is easy to cause poor high-temperature performance and mechanical performance, so as to provide a cordierite ceramic material, a preparation method thereof, and an application thereof.

[0004] The present invention provides a preparation method of a cordierite ceramic material, comprising the following steps:

[0005] 1) Mixing chromite slag and fly ash in a mass ratio of (3 - 5):(5 - 7), heating to obtain a molten mixture, and then performing water quenching treatment to obtain a frit raw material;

[0006] 2) Mix the frit raw materials obtained in step 1) with SnO2 at a mass ratio of (95 - 99):(1 - 5), grind them, and then obtain the cordierite ceramic material after calcination treatment;

[0007] The calcination treatment includes preheating, first calcination, and second calcination, and the heating rate from preheating to the first calcination is 8 - 12 °C / min.

[0008] Preferably, in step 1), the mass of the ferrochrome slag accounts for 30% - 50% of the total mass of the ferrochrome slag and fly ash;

[0009] And / or, the mass of the fly ash accounts for 50% - 70% of the total mass of the ferrochrome slag and fly ash;

[0010] And / or, the heating temperature is 1500 - 1650 °C, and the heating time is 1 - 4 h;

[0011] Optionally, the heating is carried out in an oxidizing atmosphere.

[0012] Further optionally, the heating is carried out in an air atmosphere.

[0013] Optionally, after the heating step, a clarification step is further included.

[0014] Preferably, the components of the frit raw materials in step 1), by mass percentage, include: 40 - 50% SiO2, 28 - 30% Al2O3, 3 - 5% Fe2O3, 2 - 4% CaO, 8 - 15% MgO, 3 - 6% Cr2O3, < 2% KNaO, < 2% TiO2, < 1% SO3, and the balance is loss on ignition;

[0015] Optionally, the components of the ferrochrome slag, by mass percentage, include 25 - 30% SiO2, 25 - 30% Al2O3, 3 - 5% Fe2O3, 3 - 5% CaO, 28 - 32% MgO, 8 - 10% Cr2O3, < 1% KNaO, < 1% TiO2, < 0.5% SO3, and the balance is loss on ignition;

[0016] Optionally, the components of the fly ash, by mass percentage, include 55 - 60% SiO2, 28 - 32% Al2O3, 3 - 5% Fe2O3, 2 - 4% CaO, < 1% MgO, < 2.5% KNaO, < 2% TiO2, < 0.5% SO3, and the balance is loss on ignition;

[0017] Optionally, in step 1), in the mixed particles formed by mixing the ferrochrome slag and the fly ash, more than 90 wt.% of the mixed particles have a particle size less than 30 μm.

[0018] Preferably, the grinding rotation speed in step 2) is 350 - 450 rpm, and the grinding time is 10 - 30 min;

[0019] Optionally, the grinding is carried out by wet ball milling. When wet ball milling, the mass ratio of the total mass of the frit raw material and SnO2, the grinding balls and water is 1:(1.5 - 3):(0.6 - 0.8);

[0020] Optionally, the grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 50% - 80% of the total mass of the grinding balls.

[0021] Preferably, after the grinding step in step 2), it further includes the steps of spraying an aqueous solution of polyvinyl alcohol on the ground powder for granulation, then pressing into shape and drying. After the drying step, the cordierite ceramic material is obtained after calcination treatment;

[0022] Optionally, the mass ratio of the aqueous solution of polyvinyl alcohol to the ground powder is (3 - 9):(91 - 97);

[0023] Optionally, the mass concentration of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 0.5 - 5 wt.%;

[0024] The pressure for pressing into shape is 12 - 16 MPa, and the time for pressing into shape is 20 - 60 s;

[0025] The drying temperature is 60 - 100 °C, and the drying time is 1 - 4 h.

[0026] Optionally, the average degree of polymerization of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 1600 - 2000. Further optionally, the average degree of polymerization of polyvinyl alcohol in the aqueous solution of polyvinyl alcohol is 1750. The polyvinyl alcohol used in the present invention can be obtained commercially, for example, it can be purchased from Tianjin Damao Chemical Reagent Factory.

[0027] Preferably, the preheating in step 2) includes heating at a heating rate of 2 - 4 °C / min to 550 - 600 °C;

[0028] After the preheating is completed, the first calcination is carried out. The first calcination temperature is 750 - 810 °C, and the heat preservation time for the first calcination is 1 - 8 h;

[0029] After the first calcination is completed, the second calcination is carried out. The second calcination temperature is 950 - 1050 °C, and the heat preservation time for the second calcination is 1 - 4 h;

[0030] The heating rate from the end of the first calcination to the second calcination is 1 - 3 °C / min.

[0031] Optionally, after the calcination step, a cooling step is further included.

[0032] The present invention provides a cordierite ceramic material prepared by the preparation method of the cordierite ceramic material described above.

[0033] Preferably, the cordierite phase in the cordierite ceramic material accounts for more than 95 wt.% of the total mass of the crystal phases in the cordierite ceramic material;

[0034] The magnesium aluminate spinel phase in the cordierite ceramic material accounts for 5 wt.% or less of the total mass of the crystal phases in the cordierite ceramic material.

[0035] Preferably, the average thermal expansion coefficient α of the cordierite ceramic material at 25 - 800 °C is 1.5×10 -6 -2.5×10 -6 °C -1 , the flexural strength is 55 - 70 MPa, and the bulk density is 2.30 - 2.50 g / cm 3 .

[0036] The present invention also provides an application of the cordierite ceramic material prepared by the above-mentioned preparation method or the above-mentioned cordierite ceramic material in the fields of refractory materials, precision electronic packaging materials, biomedical coating materials or chemical corrosion-resistant equipment materials.

[0037] The technical solution of the present invention has the following advantages:

[0038] 1. The preparation method of the cordierite ceramic material provided by the present invention comprises the following steps: 1) Mixing chromite slag and fly ash in a mass ratio of (3-5):(5-7), heating to obtain a molten mixture, and then performing water quenching treatment to obtain a frit raw material; 2) Mixing the frit raw material obtained in step 1) with SnO2 in a mass ratio of (95-99):(1-5), grinding, and then obtaining the cordierite ceramic material after calcination treatment; the calcination treatment includes preheating, first calcination, and second calcination, and the heating rate from preheating to the first calcination is 8-12 °C / min. The present invention uses chromite slag and fly ash in specific proportions as raw materials to prepare MgO-Al2O3-SiO2-based cordierite ceramic materials, which can realize the harmless and efficient resource utilization of chromite slag and fly ash. Chromite slag (yield 1.2-1.5 tons per ton of chromite slag) is rich in MgO, SiO2, Al2O3, and Cr2O3, and the proportion of the three components of SiO2-Al2O3-MgO reaches 82.9 wt.%. These components of chromite slag are highly matched with the chemical composition of the cordierite ceramic material. Fly ash (annual output of 490 million tons) is rich in SiO2, Al2O3, Fe2O3, and CaO. Adding fly ash to supplement the SiO2 and Al2O3 components can not only provide a silicon-aluminum source for synthesizing cordierite, but also its rich glass phase provides kinetic conditions for reducing the melting temperature and for melting-crystallization. Chromite slag and fly ash cooperate synergistically, providing a natural composition complementary advantage for preparing high-performance cordierite ceramic materials under specific dosage ratios. In terms of process optimization, the specific calcination treatment process adjustment includes preheating, first calcination, and second calcination, and at the same time, the heating rate from preheating to the first calcination is controlled to be 8-12 °C / min, maintaining a rapid heating rate from preheating to the first calcination. By shortening the residence time in the high-temperature zone, the kinetic conditions for crystal nucleus growth are restricted, and its crystallization behavior is inhibited, thereby avoiding the premature formation of the spinel phase and ensuring the controllable crystallization of the amorphous matrix of the material in subsequent heat treatment. A specific amount of SnO2 significantly improves the density, thermal stability, and erosion resistance of the material through mechanisms such as reducing the reaction temperature, regulating the crystal phase path, and inhibiting decomposition in the synthesis of cordierite. The preparation method of the cordierite ceramic material provided by the present invention has an overall process coordination, and the obtained cordierite ceramic material has a low mass content of the magnesium-aluminum spinel phase and a high mass content of the cordierite phase, and has a low thermal expansion coefficient, high flexural strength, excellent thermal stability, good high-temperature performance and mechanical properties, and can meet the requirements of special application scenarios such as high temperature, high strength, and corrosion resistance.

[0039] 2. The preparation method of the cordierite ceramic material provided by the present invention. When heating to obtain the molten mixture in step 1), the heating temperature is 1500 - 1650 °C and the heating time is 1 - 4 h; in step 2), the calcination treatment includes preheating, first calcination and second calcination. The preheating includes heating to 550 - 600 °C at a heating rate of 2 - 4 °C / min; after the preheating is completed, the first calcination is carried out. The first calcination temperature is 750 - 810 °C, and the heat preservation time of the first calcination is 2 - 8 h; after the first calcination is completed, the second calcination is carried out. The second calcination temperature is 950 - 1050 °C, and the heat preservation time of the second calcination is 1 - 4 h; the heating rate from the end of the first calcination to the second calcination is 1 - 3 °C / min. The present invention prepares the cordierite ceramic material by the method of high-temperature melting - low-temperature crystallization. The Cr2O3 contained in the ferrochrome slag can be oxidized to a highly mobile carcinogen Cr during environmental exposure 6+ , there is a risk of soil and groundwater pollution. The high-temperature melting and solidification at a specific temperature can also play a role in stabilizing Cr, fixing the Cr in the ferrochrome slag in the glass phase and crystal phase of the material, making it not easily oxidized and inhibiting the dissolution of Cr in the material. Kinetically, the selective inhibition of magnesium aluminate spinel and the precipitation of homogeneous cordierite crystals are realized by kinetic control during the frit crystallization process. The calcination treatment process can accurately regulate the thermodynamic and kinetic parameters, realize the optimization of crystal structure, size and distribution, significantly reduce the energy consumption during the preparation process, and at the same time improve the crystallization performance and mechanical properties of the material, thereby comprehensively improving the mechanical, optical and technological properties of the cordierite ceramic material. Magnesium aluminate spinel is in the crystallization stage at about 700 °C. By precisely controlling the preheating temperature and the first calcination temperature, the crystallization behavior can be accurately inhibited through a rapid heating process from the preheating to the first calcination stage (such as the heating rate > 8 °C / min in the range of 600 - 750 °C), further ensuring the controllable crystallization of the amorphous matrix of the material in subsequent heat treatment. At the same time, combined with the ratio of fly ash to ferrochrome slag and the addition of a crystallization agent, the synthesis quantity and crystal size of cordierite are further controlled. By reconstructing the synergistic effect of the thermodynamic driving force and the kinetic mass transfer conditions, a high-performance cordierite ceramic material is prepared.

[0040] 3. The preparation method of the cordierite ceramic material provided by the present invention. This process optimization not only improves the production efficiency but also significantly reduces the production cost, providing technical support for the high-value utilization of industrial solid waste. At the same time, through composition adjustment and process optimization, the microstructure and properties of the cordierite ceramic material can be further regulated to achieve customized design of the material. The obtained cordierite ceramic material has good electrical insulation performance, broad market prospects and extremely high economic value. It fills the technical gap in the preparation of cordierite ceramic materials from all-waste ferrochrome slag and fly ash.

[0041] 4. The preparation method of the cordierite ceramic material provided by the present invention provides a new technical route for the resource utilization of industrial solid wastes, and at the same time promotes green manufacturing and sustainable development through technological innovation. As the main sources of industrial solid wastes, fly ash and chromite slag not only occupy land resources during large-scale stacking, but also pose a serious threat to the environment. By converting them into cordierite ceramic materials, not only the resource utilization of waste is realized, but also the dependence on natural raw materials is significantly reduced, and the negative impact on the environment is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the specific embodiments or the prior art. Obviously, the drawings in the following description are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0043] Figure 1 XRD pattern of the chromite slag used as the raw material in the examples and comparative examples of the present invention;

[0044] Figure 2 XRD pattern of the fly ash used as the raw material in the examples and comparative examples of the present invention;

[0045] Figure 3 XRD pattern of the frit raw material prepared in Example 5 of the present invention;

[0046] Figure 4 XRD pattern of the cordierite ceramic materials prepared in Examples 2-5 of the present invention.

[0047] Figure 5 XRD pattern of the cordierite ceramic materials prepared in Example 5 and Comparative Example 3 of the present invention.

[0048] Figure 6 SEM image of the cordierite ceramic material prepared in Example 5 of the present invention.

[0049] Figure 7 SEM image of the cordierite ceramic material prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0050] The following embodiments are provided to better further understand the present invention. It is not limited to the best embodiment, and does not limit the content and protection scope of the present invention. Any product obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior art features that is the same as or similar to the present invention falls within the protection scope of the present invention.

[0051] For those embodiments where specific experimental procedures or conditions are not specified, the operations or conditions of the conventional experimental procedures described in the literature in this field can be followed. For reagents or instruments whose manufacturers are not specified, they are all conventional reagent products that can be obtained through commercial purchase.

[0052] In the polyvinyl alcohol aqueous solution used in the examples or comparative examples of the present invention, the average degree of polymerization of polyvinyl alcohol is 1750, and polyvinyl alcohol can be obtained commercially and is purchased from Tianjin Damao Chemical Reagent Factory.

[0053] The XRD pattern of the chromite slag raw material used in the examples or comparative examples of the present invention is as Figure 1 shown, and the XRD pattern of the fly ash raw material is as Figure 2 shown. The proportion of the glass phase (amorphous phase) in the chromite slag is 46 wt.%, and the crystalline phase content is 54 wt.%. Among them, the magnesium aluminate spinel phase accounts for 23.82 wt.%, and the forsterite phase accounts for 30.18 wt.%. The glass phase content in the fly ash is 66.09 wt.%, and the crystalline phase content is 33.91 wt.%. Among them, the mullite phase accounts for 25.22 wt.%, and the quartz phase accounts for 8.69 wt.%. By mass fraction, the specific components of the chromite slag and fly ash are shown in Table 1:

[0054] Table 1

[0055]

[0056]

[0057] Example 1

[0058] This example provides a method for preparing cordierite ceramic materials, including the following steps:

[0059] 1) Ball-mill and mix 30 wt.% of chromite slag and 70 wt.% of fly ash evenly to obtain mixed particles of raw materials, and the particles with a particle size less than 30 μm in the mixed particles account for more than 90 wt.% of the total mass of the mixed particles; then put the above mixed particles into a silicon molybdenum rod high-temperature furnace, heat up to 1500 °C, heat and melt the mixed particles in an air atmosphere for 4 h and clarify to obtain a molten mixture, and then pour the obtained molten mixture into water for water quenching to obtain a frit raw material; the components of the frit raw material, by mass fraction, include: 48.89% SiO2, 29.02% Al2O3, 3.33% Fe2O3, 2.93% CaO, 9.23% MgO, 2.77% Cr2O3, 1.49% KNaO, 0.98% TiO2, 0.15% SO3, 1.21% loss on ignition;

[0060] 2) After adding SnO₂ to the frit raw materials, they are placed in a planetary ball mill. The mass ratio of the frit raw materials to SnO₂ is 95:5, and then wet ball milling is carried out at a constant speed of 350 rpm at room temperature for 30 min. When wet ball milling, the mass ratio of the total mass of the frit raw materials and SnO₂, grinding balls and water is 1:1.5:0.8. The grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 80% of the total mass of the grinding balls. A polyvinyl alcohol aqueous solution with a mass concentration of 1% is sprayed on the milled powder for granulation, and the mass ratio of the polyvinyl alcohol aqueous solution to the milled powder is 3:97. Subsequently, 11 g of the granulated powder is weighed and put into a uniaxial powder press for molding to form a cuboid sample with dimensions of 60 mm × 10 mm × 10 mm (the molding pressure is 12 MPa and the molding time is 60 s). The molded sample is placed in a constant temperature drying oven at 60 °C for 4 h to remove the free water in the sample, obtaining the sample to be sintered. Calcination is carried out in an air atmosphere, and the calcination regime is: heating from room temperature to 560 °C at a heating rate of 2 °C / min, and then rapidly heating from 560 °C to 750 °C at a heating rate of 8 °C / min for the first calcination, and the holding time for the first calcination is 8 h; then heating from 750 °C to 950 °C at a heating rate of 1 °C / min for the second calcination, and the holding time for the second calcination is 4 h; finally, cooling with the furnace to obtain the cordierite ceramic material.

[0061] Example 2

[0062] This example provides a method for preparing a cordierite ceramic material, including the following steps:

[0063] 1) 40 wt.% of ferrochrome slag and 60 wt.% of fly ash are ball milled and mixed evenly to obtain mixed particles of raw materials, and the particles with a particle size less than 30 μm in the mixed particles account for more than 90 wt.% of the total mass of the mixed particles; then the above mixed particles are put into a silicon molybdenum rod high-temperature furnace, heated to 1600 °C, and heated and melted for 2 h and clarified in an air atmosphere to obtain a molten mixture; then the obtained molten mixture is poured into water for quenching to obtain frit raw materials. The components of the frit raw materials, by mass fraction, include: 45.77% SiO₂, 28.69% Al₂O₃, 3.35% Fe₂O₃, 2.97% CaO, 12.05% MgO, 3.69% Cr₂O₃, 1.33% KNaO, 0.90% TiO₂, 0.16% SO₃, 1.09% loss on ignition;

[0064] 2) After adding SnO₂ to the frit raw materials, they are placed in a planetary ball mill. The mass ratio of the frit raw materials to SnO₂ is 97:3. Then, wet ball milling is carried out at a constant speed of 400 rpm at room temperature for 20 min. When wet ball milling, the mass ratio of the total mass of the frit raw materials and SnO₂, grinding balls, and water is 1:2.0:0.7. The grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 65% of the total mass of the grinding balls. A polyvinyl alcohol aqueous solution with a mass concentration of 1% is sprayed on the milled powder for granulation. The mass ratio of the polyvinyl alcohol aqueous solution to the milled powder is 6:94. Subsequently, 11 g of the granulated powder is weighed and put into a uniaxial powder press for molding, and a cuboid sample with dimensions of 60 mm × 10 mm × 10 mm is pressed (the molding pressure is 14 MPa, and the molding time is 45 s). The pressed sample is placed in a constant-temperature drying oven at 80 °C for 2 h to remove the free water in the sample, and a sample to be sintered is obtained. Calcination is carried out in an air atmosphere, and the calcination regime is as follows: heating from room temperature to 580 °C at a heating rate of 3 °C / min, and then rapidly heating from 580 °C to 780 °C at a heating rate of 10 °C / min for the first calcination, and the holding time for the first calcination is 1 h; then heating from 780 °C to 1000 °C at a heating rate of 2 °C / min for the second calcination, and the holding time for the second calcination is 2 h; finally, cooling with the furnace to obtain the cordierite ceramic material.

[0065] Example 3

[0066] This example provides a preparation method of cordierite ceramic material, including the following steps:

[0067] 1) Mix 50 wt.% of ferrochrome slag and 50 wt.% of fly ash by ball milling evenly to obtain mixed particles of raw materials, and the particles with a particle size less than 30 μm in the mixed particles account for more than 90 wt.% of the total mass of the mixed particles; then put the above mixed particles into a silicon molybdenum rod high-temperature furnace, heat up to 1650 °C, heat and melt the mixed particles in an air atmosphere for 1 h and clarify to obtain a molten mixture; then pour the obtained molten mixture into water for quenching to obtain frit raw materials. The components of the frit raw materials, by mass fraction, include: 42.66% SiO₂, 28.37% Al₂O₃, 3.38% Fe₂O₃, 3.02% CaO, 14.88% MgO, 4.62% Cr₂O₃, 1.17% KNaO, 0.83% TiO₂, 0.18% SO₃, 0.89% loss on ignition;

[0068] 2) After adding SnO₂ to the frit raw materials, they are placed in a planetary ball mill. The mass ratio of the frit raw materials to SnO₂ is 99:1, and then dry ball milling is carried out at a constant speed of 450 rpm at room temperature for 10 min. When wet ball milling, the mass ratio of the total mass of the frit raw materials and SnO₂, grinding balls and water is 1:2.5:0.6. The grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 80% of the total mass of the grinding balls. A polyvinyl alcohol aqueous solution with a mass concentration of 1% is sprayed on the milled powder for granulation, and the mass ratio of the polyvinyl alcohol aqueous solution to the milled powder is 9:91. Subsequently, 11 g of the granulated powder is weighed and put into a uniaxial powder press for molding, and a cuboid sample with dimensions of 60 mm × 10 mm × 10 mm is pressed (the molding pressure is 16 MPa and the molding time is 30 s). The pressed sample is placed in a constant temperature drying oven at 100 °C for 1 h to remove the free water in the sample, and a sample to be fired is obtained. Calcination is carried out in an air atmosphere, and the calcination regime is as follows: heating from room temperature to 600 °C at a heating rate of 4 °C / min, and then rapidly heating from 600 °C to 810 °C at a heating rate of 12 °C / min for the first calcination, and the holding time for the first calcination is 4 h; then heating from 810 °C to 1050 °C at a heating rate of 3 °C / min for the second calcination, and the holding time for the second calcination is 1 h; finally, cooling with the furnace to obtain the cordierite ceramic material.

[0069] Example 4

[0070] This example provides a preparation method of a cordierite ceramic material, including the following steps:

[0071] 1) 50 wt.% of ferrochrome slag and 50 wt.% of fly ash are ball milled and mixed evenly to obtain mixed particles of raw materials, and the particles with a particle size less than 30 μm in the mixed particles account for more than 90 wt.% of the total mass of the mixed particles; then the above mixed particles are put into a silicon molybdenum rod high-temperature furnace, heated to 1650 °C, and heated and melted in an air atmosphere for 2 h and clarified to obtain a molten mixture; then the obtained molten mixture is poured into water for quenching to obtain frit raw materials. The components of the frit raw materials, by mass fraction, include: 42.66% SiO₂, 28.37% Al₂O₃, 3.38% Fe₂O₃, 3.02% CaO, 14.88% MgO, 4.62% Cr₂O₃, 1.17% KNaO, 0.83% TiO₂, 0.18% SO₃, 0.89% loss on ignition;

[0072] 2) After adding SnO₂ to the frit raw materials, they are placed in a planetary ball mill. The mass ratio of the frit raw materials to SnO₂ is 99:1, and then dry ball milling is carried out at a constant speed of 400 rpm at room temperature for 20 min. When wet ball milling, the mass ratio of the total mass of the frit raw materials and SnO₂, grinding balls and water is 1:2:0.7. The grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 65% of the total mass of the grinding balls. A polyvinyl alcohol aqueous solution with a mass concentration of 1% is sprayed on the milled powder for granulation, and the mass ratio of the polyvinyl alcohol aqueous solution to the milled powder is 6:94. Subsequently, 11 g of the granulated powder is weighed and put into a uniaxial powder press for molding to form a cuboid sample with dimensions of 60 mm × 10 mm × 10 mm (the molding pressure is 14 MPa and the molding time is 45 s). The molded sample is placed in a constant temperature drying oven at 80 °C for drying for 2 h to remove the free water in the sample, and a sample to be fired is obtained. Calcination is carried out in an air atmosphere, and the calcination regime is as follows: heating from room temperature to 600 °C at a heating rate of 3 °C / min, and then rapidly heating from 600 °C to 750 °C at a heating rate of 8 °C / min for the first calcination, and the holding time for the first calcination is 4 h; then heating from 750 °C to 1050 °C at a heating rate of 1 °C / min for the second calcination, and the holding time for the second calcination is 4 h; finally, cooling with the furnace to obtain the cordierite ceramic material.

[0073] Example 5

[0074] This example provides a preparation method of a cordierite ceramic material, including the following steps:

[0075] 1) 40 wt.% of ferrochrome slag and 60 wt.% of fly ash are ball milled and mixed evenly to obtain mixed particles of raw materials, and the particles with a particle size less than 30 μm in the mixed particles account for more than 90 wt.% of the total mass of the mixed particles; then the above mixed particles are put into a silicon molybdenum rod high-temperature furnace, heated to 1600 °C, and heated and melted for 2 h and clarified in an air atmosphere to obtain a molten mixture; then the obtained molten mixture is poured into water for quenching to obtain frit raw materials. The components of the frit raw materials, by mass fraction, include: 45.77% SiO₂, 28.69% Al₂O₃, 3.35% Fe₂O₃, 2.97% CaO, 12.05% MgO, 3.69% Cr₂O₃, 1.33% KNaO, 0.90% TiO₂, 0.16% SO₃, 1.09% loss on ignition;

[0076] 2) After adding SnO₂ to the frit raw materials, they are placed in a planetary ball mill. The mass ratio of the frit raw materials to SnO₂ is 97:3, and then dry ball milling is carried out at a constant speed of 400 rpm at room temperature for 20 min. When wet ball milling, the mass ratio of the total mass of the frit raw materials and SnO₂, grinding balls and water is 1:2:0.7. The grinding balls include alumina grinding balls with a particle size of 6 - 8 mm and alumina grinding balls with a particle size of 8 - 10 mm. The mass of the alumina grinding balls with a particle size of 6 - 8 mm accounts for 65% of the total mass of the grinding balls. A polyvinyl alcohol aqueous solution with a mass concentration of 1% is sprayed on the milled powder for granulation, and the mass ratio of the polyvinyl alcohol aqueous solution to the milled powder is 6:94. Subsequently, 11 g of the granulated powder is weighed and put into a uniaxial powder press for molding to form a cuboid sample with dimensions of 60 mm × 10 mm × 10 mm (the molding pressure is 16 MPa and the molding time is 30 s). The pressed sample is placed in a constant temperature drying oven at 80 °C for 2 h to remove the free water in the sample, and a sample to be fired is obtained. Calcination is carried out in an air atmosphere, and the calcination regime is: heating from room temperature to 600 °C at a heating rate of 3 °C / min, and then rapidly heating from 600 °C to 780 °C at a heating rate of 10 °C / min for the first calcination, and the holding time for the first calcination is 8 h; then heating from 780 °C to 1000 °C at a heating rate of 2 °C / min for the second calcination, and the holding time for the second calcination is 2 h; finally, cooling with the furnace to obtain the cordierite ceramic material.

[0077] Comparative Example 1

[0078] This comparative example provides a preparation method of cordierite ceramic material. The difference from Example 5 is only that in step 1), the raw material mixed particles obtained by ball milling and mixing 40 wt.% of ferrochrome slag and 60 wt.% of fly ash evenly are replaced by the raw material mixed particles obtained by ball milling and mixing 60 wt.% of ferrochrome slag and 40 wt.% of fly ash evenly.

[0079] Comparative Example 2

[0080] This comparative example provides a preparation method of cordierite ceramic material. The difference from Example 5 is only that in step 2), the mass ratio of the frit raw materials to SnO₂ is replaced by 90:10.

[0081] Comparative Example 3

[0082] This comparative example provides a preparation method of cordierite ceramic material. The difference from Example 5 is only that in step 2), the first calcination of rapidly heating from 600 °C to 780 °C at a heating rate of 10 °C / min is replaced by the first calcination of rapidly heating from 600 °C to 780 °C at a heating rate of 3 °C / min.

[0083] Comparative Example 4

[0084] This comparative example provides a method for preparing a cordierite ceramic material, which differs from Example 5 only in that an equal mass of fly ash is used to replace ferrochrome waste slag in step 1).

[0085] Comparative Example 5

[0086] This comparative example provides a method for preparing a cordierite ceramic material, which differs from Example 5 only in that an equal mass of ferrochrome waste slag is used to replace fly ash in step 1).

[0087] Comparative Example 6

[0088] This comparative example provides a method for preparing a cordierite ceramic material, which differs from Example 5 only in that an equal mass of kaolin (the kaolin components and mass contents are shown in Table 2) is used in step 1) to replace fly ash.

[0089] Table 2

[0090]

[0091] Comparative Example 7

[0092] This comparative example provides a method for preparing a cordierite ceramic material, which differs from Example 5 only in that an equal mass of TiO2 is used to replace SnO2 in step 2).

[0093] Test Case

[0094] The frit raw material prepared in Example 5 was subjected to an XRD scanning test, and the obtained XRD pattern was as follows: Figure 3 As shown; the cordierite ceramic materials prepared in Examples 2-5 and Comparative Example 3 were subjected to XRD scanning tests, and the XRD patterns obtained in Examples 2-5 were as shown Figure 4 As shown, the XRD patterns of the cordierite ceramic materials prepared in Example 5 and Comparative Example 3 are as follows Figure 5 The cordierite ceramic materials prepared in Example 5 and Comparative Example 3 were subjected to SEM scanning tests. The SEM images obtained in Example 5 are as shown in FIG. Figure 6 As shown, the SEM image obtained in Comparative Example 3 is as follows Figure 7 shown.

[0095] The cordierite ceramic materials prepared in Examples 1-5 and Comparative Examples 1-7 were used as the test samples to determine the mass content of each crystalline phase using the K value internal standard method (also known as the reference intensity method). The specific steps were: (1) selecting corundum (α-Al2O3, JCPDS-43-1484) as the standard substance; (2) mixing the test sample with corundum in a mass ratio of 4:1 (20 wt.%) and preparing a mixed sample by fully grinding; (3) determining the reference intensity of each phase according to the relative intensity ratio (RIR) provided by the JCPDS card. (4) Process the diffraction data using Jade 6.5 software, and calculate the content of each crystal phase by combining formulas (1-1), (1-2), and (1-3). Data processing: Phase identification: Perform matching through the ICDD database. Quantitative calculation:

[0096]

[0097] In formulas (1-1), (1-2), and (1-3): I j : The intensity of the strongest diffraction peak of phase j (phase j is the crystal phase to be measured) in the mixed sample, I s : The intensity of the strongest diffraction peak of the standard substance (corundum), K s J : The reference intensity ratio (RIR value) of phase j relative to the standard substance, w j ’: The mass fraction of phase j in the mixed sample, w s ’: The mass fraction of the standard substance in the mixed sample (fixed at 20%), w j : The mass fraction of phase j in the original sample, ∑w t : The total mass fraction of each crystal phase in the original sample, w t : The mass fraction of phase j in the crystal phase in the original sample. The measurement results of the mass content of each crystal phase in the crystal phase are shown in Table 3.

[0098] Use a PCY2 type thermal dilatometer produced by Hunan Xiangyi Instrument Company to measure the average thermal expansion coefficient (α) of the cordierite ceramic materials prepared in Examples 1-5 and Comparative Examples 1-7 at 25-800 °C by the push rod method. The measurement results are shown in Table 3.

[0099] Use a microcomputer-controlled universal testing machine of WDW-20 to measure the flexural strength value of the cordierite ceramic materials prepared in Examples 1-5 and Comparative Examples 1-7 by the three-point bending method. The span is 30 mm. The test method refers to the test standard of GB / T4741-1999. The measurement results are shown in Table 3.

[0100] According to the standard of QB / T 1642-2012, use the boiling method in the standard to measure the bulk density of the cordierite ceramic materials prepared in Examples 1-5 and Comparative Examples 1-7. The measurement results are shown in Table 3.

[0101] Table 3

[0102]

[0103]

[0104] Among the measurement results of the mass content of the crystal phase, the crystal phase of Comparative Example 4 is 75.60% mullite phase and 24.40% quartz phase respectively; the remaining crystal phase of Comparative Example 5 is quartz phase; the remaining crystal phase of Comparative Example 6 is quartz phase; the remaining crystal phase of Comparative Example 7 is protoenstatite phase.

[0105] Obviously, the above embodiments are only examples given for clear illustration, rather than limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or alterations can be made based on the above description. It is not necessary and impossible to enumerate all the implementation manners here. And the obvious changes or alterations derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a cordierite ceramic material, characterized in that: The following steps are involved: 1) mixing ferrochrome waste slag and fly ash in a mass ratio of (3-5):(5-7), heating to obtain a molten mixture, and then quenching with water to obtain a frit raw material; 2) mixing the frit raw material obtained in step 1) with SnO2 in a mass ratio of (95-99):(1-5), grinding, and calcining to obtain the cordierite ceramic material; The calcination process includes preheating, first calcination and second calcination, and the heating rate from preheating to first calcination is 8-12°C / min.

2. The method for preparing the cordierite ceramic material according to claim 1, characterized in that: The mass of the ferrochrome waste slag in step 1) accounts for 30%-50% of the total mass of the ferrochrome waste slag and fly ash; And / or, the mass of the fly ash accounts for 50%-70% of the total mass of the ferrochrome waste slag and the fly ash; And / or, the heating temperature is 1500-1650° C., and the heating time is 1-4 hours; Optionally, the heating is carried out in an oxidizing atmosphere.

3. The method for preparing the cordierite ceramic material according to claim 1 or 2, characterized in that: The components of the frit raw material in step 1) include, by mass percentage, 40-50% SiO2, 28-30% Al2O3, 3-5% Fe2O3, 2-4% CaO, 8-15% MgO, 3-6% Cr2O3, <2% KNaO, <2% TiO2, <1% SO3, and the balance is loss on ignition; Optionally, the components of the ferrochrome waste slag, by mass percentage, include 25-30% SiO2, 25-30% Al2O3, 3-5% Fe2O3, 3-5% CaO, 28-32% MgO, 8-10% Cr2O3, <1% KNaO, <1% TiO2, <0.5% SO3, and the balance is loss on ignition; Optionally, the components of the fly ash, by mass percentage, include 55-60% SiO2, 28-32% Al2O3, 3-5% Fe2O3, 2-4% CaO, <1% MgO, <2.5% KNaO, <2% TiO2, <0.5% SO3, and the balance is loss on ignition; Optionally, in the mixed particles formed by mixing the ferrochrome waste slag and the fly ash in step 1), more than 90 wt.% of the mixed particles have a particle size of less than 30 μm.

4. The method for preparing the cordierite ceramic material according to any one of claims 1 to 3, characterized in that: The grinding speed in step 2) is 350-450 rpm, and the grinding time is 10-30 min; Optionally, the grinding is performed by wet ball milling, and the mass ratio of the total mass of the frit raw material and SnO2, the mass of the grinding balls and the water during the wet ball milling is 1:(1.5-3):(0.6-0.8); Optionally, the grinding balls include alumina grinding balls with a particle size of 6-8 mm and alumina grinding balls with a particle size of 8-10 mm, and the mass of the alumina grinding balls with a particle size of 6-8 mm accounts for 50%-80% of the total mass of the grinding balls.

5. The method for preparing the cordierite ceramic material according to any one of claims 1 to 4, characterized in that: After the grinding step in step 2), the powder is sprayed with a polyvinyl alcohol aqueous solution to form granules, followed by pressing and drying. After the drying step, the powder is calcined to obtain the cordierite ceramic material. Optionally, the mass ratio of the polyvinyl alcohol aqueous solution to the ground powder is (3-9): (91-97); Optionally, the mass concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 0.5-5wt.%; The pressing pressure is 12-16 MPa, and the pressing time is 20-60 s; The drying temperature is 60-100° C., and the drying time is 1-4 hours.

6. The method for preparing the cordierite ceramic material according to any one of claims 1 to 5, characterized in that: The preheating in step 2) includes heating to 550-600° C. at a heating rate of 2-4° C. / min; After the preheating is completed, the first calcination is performed, the first calcination temperature is 750-810° C., and the first calcination insulation time is 1-8 hours; After the first calcination, a second calcination is performed, the second calcination temperature is 950-1050° C., and the second calcination holding time is 1-4 hours; The heating rate from the first calcination to the second calcination is 1-3°C / min.

7. A cordierite ceramic material, characterized in that: The cordierite ceramic material is prepared by the preparation method of the cordierite ceramic material according to any one of claims 1 to 6.

8. The cordierite ceramic material according to claim 7, characterized in that: The cordierite phase in the cordierite ceramic material accounts for more than 95wt.% of the total mass of the crystalline phase in the cordierite ceramic material; The magnesia-alumina spinel phase in the cordierite ceramic material accounts for less than 5 wt.% of the total mass of the crystal phase in the cordierite ceramic material.

9. The cordierite ceramic material according to claim 7 or 8, characterized in that: The average thermal expansion coefficient α of the cordierite ceramic material at 25-800°C is 1.5×10 -6 -2.5×10 -6 ℃ -1 , flexural strength is 55-70MPa, volume density is 2.30-2.50g / cm 3 .

10. The cordierite ceramic material prepared by the preparation method according to any one of claims 1 to 6 or the cordierite ceramic material according to any one of claims 7 to 9 is used in the fields of refractory materials, precision electronic packaging materials, biomedical coating materials or chemical anti-corrosion equipment materials.

Citation Information

Patent Citations

  • Floor tile applicable to laying of floor heating system and manufacturing method thereof

    CN106082972A

  • Cordierite microcrystalline glass prepared from high carbon ferrochrome slag and coal gangue and preparation method of cordierite microcrystalline glass

    CN106698954A

  • High-intensity porcelain architectural-pottery archaized brick prepared from two waste residues compositely

    CN107140945A

  • Method for preparing cordierite ceramic from fly ash

    CN115321971A

  • Treatment of incineration ash of combustible waste

    JP1995060229A